Comparison of the solvency levels between conventional banks and Islamic banks. - Tan, Ying Guang. (2011)
In the aftermath of the recent financial crisis, bank solvency levels have been determined as one of the most important factors contributing to a stabilized global economy. As such, this paper endeavours to study how solvency levels differ between Islamic banks and conventional banks.